Identification and characterization of the bacteriocin Carocin S3 from the multiple bacteriocin producing strain of Pectobacterium carotovorum subsp. carotovorum - Wang, Jyun-Wei; Derilo, Reymund C.; Lagitnay, Ruchi Briam James S.; Wu, Huang-Pin; Chen, Kai-In; Chuang, Duen-Yau (BMC microbiology, 2020)
Pectobacterium carotovorum subsp. carotovorum belongs to the Enterobacteriaceae family, which causes soft-rot disease in numerous plants worldwide resulting in significant economic losses. Results from our previous studies showed that the strain H-rif-8-6 produces low-molecular-weight bacteriocin (LMWB) Carocin S1. Interestingly, TH22-10, the caroS1K:Tn5 insertional mutant in H-rif-8-6, loses Carocin S1 producing ability, but still produces other LMWBs which the indicator strain SP33 can detect. The SP33 is one of the many strains that are sensitive toward the cytotoxic effects of Carocin S3K, but not Carocin S1. The result revealed that H-rif-8-6 is a multiple-bacteriocin producing strain. In this study, a 4.1-kb DNA fragment was isolated from the chromosomal DNA of Pcc strain, H-rif-8-6, by a DNA probe using the caroS1K gene as the template. DNA sequencing and analysis by GenBank revealed two complete open reading frames (ORFs), designated ORF1 and ORF2, which were identified within the sequence fragment. ORF1 and ORF2, similar to the identified carocin S2 genes, encode the killer (Carocin S3K) and the immunity (Carocin S3I) proteins, respectively, which were homologous to the colicin E3 gene. Carocin S3K and Carocin S3I were expressed, isolated, and purified in Escherichia coli BL21 after subcloning of the expression plasmid pGS3KI or pGSK3I. SDS-PAGE analysis showed that the relative masses of Carocin S3K and Carocin S3I were 95.6 kDa and 10.2 kDa, respectively. The results reveal that Carocin S3K has higher antimicrobial and specific antimicrobial activities for Pcc along with a nuclease activity than Carocin S3I. However, Carocin S3I inhibits the activity of Carocin S3K. Interestingly, a high concentration of Carocin S3I protein is also a DNA nuclease, and Carocin S3K also inhibits its activity. This study showed that another type of bacteriocin was found in Pectobacterium carotovorum. This new type of bacteriocin, Carocin S3, has the killer protein, Carocin S3K, and the immunity protein, Carocin S3I.